Metasurfaces Atop Metamaterials: Surface Morphology Induces Linear Dichroism in Gyroid Optical Metamaterials. Issue 2 (4th November 2018) - Dolan, James A.; Dehmel, Raphael; Demetriadou, Angela; Gu, Yibei; Wiesner, Ulrich; Wilkinson, Timothy D.; Gunkel, Ilja; Hess, Ortwin; Baumberg, Jeremy J.; Steiner, Ullrich; Saba, Matthias; Wilts, Bodo D.
Abstract: Optical metamaterials offer the tantalizing possibility of creating extraordinary optical properties through the careful design and arrangement of subwavelength structural units. Gyroid‐structured optical metamaterials possess a chiral, cubic, and triply periodic bulk morphology that exhibits a redshifted effective plasma frequency. They also exhibit a strong linear dichroism, the origin of which is not yet understood. Here, the interaction of light with gold gyroid optical metamaterials is studied and a strong correlation between the surface morphology and its linear dichroism is found. The termination of the gyroid surface breaks the cubic symmetry of the bulk lattice and gives rise to the observed wavelength‐ and polarization‐dependent reflection. The results show that light couples into both localized and propagating plasmon modes associated with anisotropic surface protrusions and the gaps between such protrusions. The localized surface modes give rise to the anisotropic optical response, creating the linear dichroism. Simulated reflection spectra are highly sensitive to minute details of these surface terminations, down to the nanometer level, and can be understood with analogy to the optical properties of a 2D anisotropic metasurface atop a 3D isotropic metamaterial. This pronounced sensitivity to the subwavelength surface morphology has significant consequences for both the design and application of optical metamaterials. Abstract : Gyroid‐structured 3D optical metamaterials exhibit extraordinary optical properties due to the subwavelength chiral, cubic, and triply periodic bulk morphology. However, the surface morphology of the gyroid structure breaks the cubic symmetry, resulting in a strong linear dichroism, which can be modeled as an anisotropic metasurface atop an isotropic metamaterial. This has important consequences for the design of 3D optical metamaterials.